2009
DOI: 10.1007/s12298-009-0030-x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of S-adenosyl-L-methionine synthetase gene from Panax ginseng C.A. meyer and analysis of its response to abiotic stresses

Abstract: A cDNA clone containing a S-adenosyl-L-methionine synthetase (SAMS) gene, named as PgSAM, was isolated from a commercial medicinal plant Panax ginseng. PgSAM is predicted to encode a precursor protein of 307 amino acid residues, and its sequence shares high homology with a number of other plant SAMS. PgSAM is expressed at different levels in various organs of ginseng. The expression of PgSAM in adventitious roots and hairy roots of P. ginseng were analyzed using reverse transcriptase (RT)-PCR and real-time PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…The only active methyl cycle enzyme not identified in the hypersalinity dataset was METsyn whose gel resolution was limited by its large size. Previous studies have also documented salinity-induced increases in SAMsyn genes Pulla et al, 2009). SAMsyn is responsible for the regeneration of SAM, the required cofactor for the penultimate methyltransferase reaction in DMSP synthesis.…”
Section: Candidate Dmsp Synthesis Enzymesmentioning
confidence: 89%
“…The only active methyl cycle enzyme not identified in the hypersalinity dataset was METsyn whose gel resolution was limited by its large size. Previous studies have also documented salinity-induced increases in SAMsyn genes Pulla et al, 2009). SAMsyn is responsible for the regeneration of SAM, the required cofactor for the penultimate methyltransferase reaction in DMSP synthesis.…”
Section: Candidate Dmsp Synthesis Enzymesmentioning
confidence: 89%
“…Members of this family of protein are also regulated by stress-responsive TFs (Chen et al 2006 ). Pulla et al ( 2009 ) reported that S -adenosyl-L -methionine synthetase (SAMS) gene of Panax ginseng ( PgSAM ) expressed under various abiotic stresses in Panax ginseng and might be providing protection against environmental stresses.…”
Section: Gene Expression and Regulation In Response To Abiotic Stressesmentioning
confidence: 99%
“…PcSAMS1 is specific to root growth and formation, while PcSAMS2 functions more generally during plant growth (Lindroth et al 2001). SAMS from Panax ginseng was significantly under salt, salicylic acid, abscisic acid and chilling stresses (Pulla et al 2009). PySAMS gene isolated from Porphyra yezoensis was known to be stress related gene.…”
Section: Amino Acid Sequence Analysis and Alignmentmentioning
confidence: 99%